2016
DOI: 10.3892/mmr.2016.4772
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylated chitosan protects rat chondrocytes from NO-induced apoptosis via inhibition of the p38/MAPK signaling pathway

Abstract: In the present study, the effect of carboxymethylated chitosan (CMCS) on nitric oxide (NO)‑induced apoptosis, and activation of the p38/MAPK signaling pathway in chondrocytes were investigated. Cartilage was isolated from the knee joints of Sprague‑Dawley rats, and was used to establish cultured primary chondrocytes. The chondrocytes were incubated with the NO donor, sodium nitroprusside (SNP), to induce apoptosis, and were treated with CMCS and the p38 inhibitor, SB203580. Cell viability was assessed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The present study showed that CS or HA-CS slightly but not significantly changed the gene and protein levels of Bcl-2, Bax, and caspase-3. Our data agree with the previous reports [38, 39]. In addition, the expression of Bcl-2 was significantly increased in the CS-IL-1Ra and HA-CS-IL-1Ra groups, while the expressions of Bax and caspase-3 were decreased at the transcriptional and translational levels compared with those in the control group, with HA-CS-IL-1Ra having slightly more potent effect than CS-IL-1Ra.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that CS or HA-CS slightly but not significantly changed the gene and protein levels of Bcl-2, Bax, and caspase-3. Our data agree with the previous reports [38, 39]. In addition, the expression of Bcl-2 was significantly increased in the CS-IL-1Ra and HA-CS-IL-1Ra groups, while the expressions of Bax and caspase-3 were decreased at the transcriptional and translational levels compared with those in the control group, with HA-CS-IL-1Ra having slightly more potent effect than CS-IL-1Ra.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we can inhibit the NO production to protect mitochondrial functions and can decrease the chondrocyte apoptosis rate. Moreover much evidence suggests that the mediators including hyper production of NO have been proposed to be necessary for activation of the p38/MAPK signaling pathway in chondrocytes [32,33]. In our study, COS can suppress the mRNA expression levels of iNOS.…”
Section: Discussionmentioning
confidence: 52%
“…CMCS has been widely studied in OA related diseases in recent years in vivo and in vitro in recent days [15][16][17]. We have also used CMCS in cultured chondrocytes and found CMCS also has the inhibitory effect on NO-induced apoptosis in cultured chondrocytes [18,19].…”
Section: Introductionmentioning
confidence: 92%
“…The isolation and identification of primary chondrocytes from SD rats according to the previously described [18,19]. The experimental protocols were approved by Animal Ethics Committee of Wuhan University (Wuhan, China).…”
Section: Cell Culture and Identificationmentioning
confidence: 99%
See 1 more Smart Citation